Description of students learning difficulties in the atomic structure - Nesha Putri Adi; Fajriah Azra (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2023)
Atomic structure material is studied by high school students in class X in odd semesters. In this material, as much as 66.81% of class X students of SMAN 13 Padang have yet to achieve the minimum criteria set. It indicates that students have learning difficulties. Learning difficulties are failures in achieving learning goals characterized by low learning outcomes. This study aims to determine the percentage of learning difficulties experienced by students in atomic structure material and determine the factors that cause students' learning difficulties in terms of learning methods. This research is a type of descriptive research. The sample for this research was 36 students in class X E3 of SMAN 13 Padang in the 2022/2023 academic year. The research instrument was a diagnostic test with two-tier multiple-choice questionnaires and interviews. The data analysis used is descriptive, namely analyzing and providing an understanding of the data in the form of numbers so that an overview can be given in an orderly, concise, and clear manner. The results of this study stated that students of SMAN 13 Padang experienced learning difficulties in atomic structure material with a high category. The highest difficulty level is found in the fourth indicator (Determining electron configurations and quantum numbers), which is 81.25%. Learning difficulties experienced by students are caused by ineffective learning methods, such as not making a study schedule and not carrying it out, not reading and not taking notes, not repeating material, not concentrating on learning, and not doing assignments.